2005
DOI: 10.1161/01.res.0000168327.22888.4d
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-Induced Myocardial Dysfunction

Abstract: Abstract-The pathophysiology of sepsis-induced myocardial dysfunction still remains controversial. Macrophage migration inhibitory factor (MIF) has recently been identified as a cardiac-derived myocardial depressant factor in septic shock. Putative mechanisms by which MIF affects cardiac function are unknown. In an investigation of possible mechanisms of action, a rat model of endotoxin toxicity was designed using intraperitoneal (I/P) injection of lipopolysaccharides (LPS) with or without coinfusion of neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 44 publications
1
56
0
Order By: Relevance
“…This is in agreement with already published data indicating significant inhibition of pro-apoptotic potential (BAX/Bcl-2 ratio) after MIF protein inhibition in cardiomyocytes observed both in vivo and in vitro. 26,28 Interestingly, although ISO-1 demonstrated protective effect on pancreatic islets, it upregulated caspase 3 and BIM expressions. This could be only a transient increase detected after 6 h Figure 5 For caption see page 693.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This is in agreement with already published data indicating significant inhibition of pro-apoptotic potential (BAX/Bcl-2 ratio) after MIF protein inhibition in cardiomyocytes observed both in vivo and in vitro. 26,28 Interestingly, although ISO-1 demonstrated protective effect on pancreatic islets, it upregulated caspase 3 and BIM expressions. This could be only a transient increase detected after 6 h Figure 5 For caption see page 693.…”
Section: Discussionmentioning
confidence: 95%
“…[31][32][33] However, MIF acts as a pro-apoptotic molecule as well through engaging mitochondriarelated apoptotic pathway. [25][26][27][28] The initial step in the apoptosis induction is assembling of BAX molecules into large homo-oligomers that damage the outer mitochondrial membrane, consequently becoming permeable to proteins normally constrained within the intermembrane space of the mitochondria. On the other hand, presence of Bcl-2 proteins confronts membrane pore formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To test this, we examined the effect of MIF/TTX DNA vaccination on the mRNA levels of inflammatory cytokines in the lung tissues of mice with sepsis. As neutralization of MIF was reported to be associated with decreased mRNA expressions of IL-1b and IL-6 in LPS-induced rat myocardial dysfunction model, 25 mRNA levels of these proinflammatory cytokines were also measured. We found that MIF/TTX DNA vaccination suppressed TNF, IL-1b and IL-6 expression in the lung upon challenge with LPS or CLP.…”
Section: Mif/ttx Dna Vaccination and Sepsis S Tohyama Et Almentioning
confidence: 99%